ANALYSIS OF TERMINAL TRUCK EFFECTIVENESS WITH OVERALL EQUIPMENT EFFECTIVENESS - Muhammad Kareza Abrianto; Devina Puspita Sari; Renanda Nia Rachmadita (Universitas Ahmad Dahlan Indonesia, 2021)
As a service company, service quality and speed of service are the main focuses of the company. One equipment in loading and unloading is Terminal Truck. However, Terminal Truck currently has less than desirable with the frequent occurrence of breakdown. This will have an impact on the time used to be less productive. This study aims to determine the effectiveness of the Terminal Truck by using Overall Equipment Effectiveness (OEE). The results of this study found that the CTT was still below the standard set by JIPM, namely 85%. Meanwhile losses, the significant that affect the effectiveness of CTT are idling and minor stoppage losses.